2020
DOI: 10.17582/journal.aavs/2020/8.10.1100.1108
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reproductive Efficiency and Herd Dynamics of Local Cattle Breeds in Benadir Region, Somalia

Abstract: Reproductive performance is one of the most important economic traits in beef or dairy production. The majority (60%) of Somalis are pastoral nomads and engage livestock production for livelihood, employment and income. Recurrent droughts and diseases are discouraging the pastoral production systems and forcing some pastoralists and diaspora to adopt small scale dairy production. Measuring the reproductive efficiency of dairy production in Somalia is paramount and deemed necessary. Therefore, an assessment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Climatic factors, variety of breeds and management practices were responsible for the inconsistency of age to attain puberty (Agere et al., 2012). Another factor that hinders the development of favourable conditions for puberty is disease (Hassan et al., 2020). B. indicus (indigenous cattle) in the tropics and subtropics are thought to reach puberty between the ages of 16 and 40 months (Tiruneh & Taddie, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climatic factors, variety of breeds and management practices were responsible for the inconsistency of age to attain puberty (Agere et al., 2012). Another factor that hinders the development of favourable conditions for puberty is disease (Hassan et al., 2020). B. indicus (indigenous cattle) in the tropics and subtropics are thought to reach puberty between the ages of 16 and 40 months (Tiruneh & Taddie, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that hinders the development of favourable conditions for puberty is disease (Hassan et al, 2020) (2012) 6.46 ± 0.13 for Horro breed, Chali (2014) 7.0 ± 0.2 for Arsi breed. Similarly, current study showed a higher calf yield than three to four calves of average indigenous cow at national level (Galmessa & Fita, 2019).…”
Section: 7mentioning
confidence: 99%
“…Moreover, training of BCS and the importance of supplementation to maintain BCS primarily at the beginning of the breeding season to support pregnancy requirements and post-calving for support of estrus is encouraged [ 55 ]. These interventions may not only assist beef cattle smallholders in SA but other tropical countries such as Somalia, Vietnam, and Indonesia reporting similar results [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fungi effects on the natural ecosystem and pastures were also reported also to reduce pasture biomass yield and quality [31] and therefore create further shortage of pastures for pregnant cattle. Inadequate availability of quality feed resources in the grazing areas between December and January is a major reason for low mean calf birth weight during the June to August calving season [32][33][34]. Moreover, it contributes to livestock illness, mortality cases, low production output and animal productivity [32,35].…”
Section: Discussionmentioning
confidence: 99%